Port Service Bottlenecks and Shipping Agency Performance in Banten: A Qualitative Analysis - Putri Dwi Jayanti; Mardiana, Mardiana; Boy Laksmana; Sukardi, Sukardi; Rajes Kahardianto (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
This research explores how pilotage-tug assistance, cargo-handling efficiency, and document-processing duration affect the operational performance of PT. Berkah Tata Baruna, Branch Banten. Adopting a qualitative descriptive design, the study utilized interviews, focus group discussions, and analysis of official documents to capture a wide range of stakeholder perspectives, including port authorities, shipping agents, and maritime cadets. The collected data were examined through thematic analysis and further consolidated into two evaluative measures: the Port Call Friction Index (PCFI) and the Agency Performance Score (APS). The findings indicate that shortcomings in tug services, loading-unloading productivity, and administrative procedures impose considerable limitations on agency effectiveness, even though the overall performance assessment remains generally favorable. Beyond these operational insights, the study contributes to the literature on maritime economy and sustainability by presenting practical diagnostic instruments that can be applied in similar contexts. Furthermore, it strengthens the relevance of vocational maritime education by linking theoretical learning with the realities of port operations. The results also emphasize the pressing need for stronger coordination among stakeholders, simplification of documentation workflows, and systematic training programs designed to enhance professional competence. By addressing these areas, shipping agencies and port authorities can improve service delivery, minimize delays, and foster sustainable practices that align with the broader objectives of maritime development.